Interfaith Marriage Among the Tengger-Tosari Community in Pasuruan: Between Religious Normativity and Cultural Reality - Nor Salam; Irwan Supriadin J (STIT Sunan Giri Bima, 2025)
The focus of this article is to discuss the reality of interfaith marriages that occur among the Tengger-Tosari community in Pasuruan, in addition to the pattern of legal smuggling they do to obtain legal recognition of interfaith marriages. This is an interesting topic to study in order to complement general studies on interfaith marriage that tend to focus only on formal legal issues. Therefore, this research uses a socio-legal research model, which is a combination of doctrinal legal research methods and empirical legal research. Through this method, it is concluded that legal avoidance through submission to one of the prospective partner's religions is the main avoidance model among the Tengger Tosari community. However, this conversion is not permanent, because data from interviews with informants show that after the marriage takes place, they tend to return to their original religion. so the disposition of this research illustrates interesting field facts. in the future, researchers can enrich similar research by describing quantitative data that can be approached with mixed method research to find the exact number and perceptions of the perpetrators of interfaith marriages.